Phthalate Exposure Changes the Metabolic Profile of Cardiac Muscle Cells - Posnack, Nikki Gillum (National Institute of Environmental Health Sciences, 2012)
Background: Phthalates are common plasticizers present in medical-grade plastics and other everyday products. They can also act as endocrine-disrupting chemicals and have been linked to the rise in metabolic disorders. However, the effect of phthalates on cardiac metabolism remains largely unknown. Objectives: We examined the effect of di(2-ethylhexyl)phthalate (DEHP) on the metabolic profile of cardiomyocytes because alterations in metabolic processes can lead to cell dysfunction. Methods: Neonatal rat cardiomyocytes were treated with DEHP at a concentration and duration comparable to clinical exposure (50–100 μg/mL, 72 hr). We assessed the effect of DEHP on gene expression using microarray analysis. Physiological responses were examined via fatty acid utilization, oxygen consumption, mitochondrial mass, and Western blot analysis. Results: Exposure to DEHP led to up-regulation of genes associated with fatty acid transport, esterification, mitochondrial import, and β-oxidation. The functional outcome was an increase in myocyte fatty acid–substrate utilization, oxygen consumption, mitochondrial mass, PPARα (peroxisome proliferator-activated receptor α) protein expression, and extracellular acidosis. Treatment with a PPARα agonist (Wy-14643) only partially mimicked the effects observed in DEHP-treated cells. Conclusions: Data suggest that DEHP exposure results in metabolic remodeling of cardiomyocytes, whereby cardiac cells increase their dependence on fatty acids for energy production. This fuel switch may be regulated at both the gene expression and posttranscription levels. Our findings have important clinical implications because chronic dependence on fatty acids is associated with an accumulation in lipid intermediates, lactate, protons, and reactive oxygen species. This dependence can sensitize the heart to ischemic injury and ventricular dysfunction.